One of the minor gods: A case study on Khentytjenenet, an Old Kingdom deity of the Memphite necropolis - Veronika Dulíková (Pražské Egyptologické Studie, 2016)
Hitherto sparse evidence on Khentytjenenet has been markedly enlarged owing to new excavations of the Czech archaeological mission at Abusir. A recently discovered cluster of individuals holding priestly titles and/or epithets referring to Khentytjenenet has given us an impetus to scrutinise this deity. Records of Khentytjenenet are closely connected with a specific geographical part of the Memphite necropolis – Abusir and North Saqqara. The appearance of this deity was obviously associated with social, religious and administrative changes during the reign of Nyuserre. The title “hem-netjer-priest of Khentytjenet” appeared for the first time in the titulary of the high priest Ptahshepses, buried at North Saqqara (C1), and simultaneously within personal names of individuals who held offices under Nyuserre and were buried at Abusir or North Saqqara. Whereas personal names compounded with the element Khentytjenenet were characteristic for the mid-Fifth Dynasty, the title hem-netjer-priest and epithet imakhu kher linked with Khentytjenet occurred in the Sixth Dynasty. His name was also the component of several names of royal domains and estates in the late Fifth and early Sixth Dynasty.